Thermodynamically stable [4 + 2] cycloadducts of lanthanum-encapsulated endohedral metallofullerenes - Takano, Yuta; Nagashima, Yuki; Herranz, M. Ángeles; Martín, Nazario; Akasaka, Takeshi (Beilstein Journal of Organic Chemistry, 2014)
The [4 + 2] cycloaddition of o-quinodimethanes, generated in situ from the sultine 4,5-benzo-3,6-dihydro-1,2-oxathiin 2-oxide and its derivative, to La metal-encapsulated fullerenes, La2@C80 or La@C82, afforded the novel derivatives of endohedral metallofullerenes (3a,b, 4a,b and 5b). Molecular structures of the resulting compounds were elucidated using spectroscopic methods such as MALDI–TOF mass, optical absorption, and NMR spectroscopy. The [4 + 2] adducts of La2@C80 (3a,b, and 4a,b) and La@C82 (5b), respectively, retain diamagnetic and paramagnetic properties, as confirmed by EPR spectroscopy. Dynamic NMR measurements of 4a at various temperatures demonstrated the boat-to-boat inversions of the addend. In addition, 5b revealed remarkable thermal stability in comparison with the reported [4 + 2] cycloadduct of pentamethylcyclopentadiene and La@C82 (6). These findings demonstrate the utility of sultines to afford thermodynamically stable endohedral metallofullerene derivatives for the use in material science.
Keywords: carbon nanomaterials; dynamic NMR; endofullerenes; La2@C80; La@C82; sultine